Pengaruh Kombinasi Jarak Tanam Dan Pupuk Fosfat (SP-36) Terhadap Pertumbuhan Dan Produksi Tanaman Jagung (Zea Mays L.) Hibrida P21 Pada Tanah Ultisol - anggi Cahyana; Muhammad Syafi'i; Muhammad Yamin Samaullah (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
Yield of corn production can be increased by managing spacing and providing optimal dosages of phosphate fertilizers. This study aimed to find a combination of SP-36 fertilizer dosage and spacing that was able to produce the best results for P21 hybrid maize on ultisol soil in Kuningan. The experimental design used was a randomized block design, consisting of 16 treatments and 3 replications. The treatments consisted of 4 spacing (60 x 25cm, 70 x 25cm, 80 x 25cm, 90 x 25cm) combined with 4 doses of SP-36 fertilizer (0 kg / ha, 100 kg / ha, 200 kg / ha, 300 kg /Ha). Data were analyzed using analysis of variance and Duncan's multiple range test at the 5% level. The results showed that the combination of spacing and dosage of SP-36 fertilizer had a significant effect on growth in height, stem diameter, yield, weight of cob without husks, and shell weight per hectare. The combination of spacing and SP-36 (90 x 25cm and 300 kg / ha) gave the best results on number of leaves, stem diameter, leaf area, age of male flowers, age of female flowers, ear height, ear length, harvest ear diameter, number of rows. ear, ear weight with ear, ear weight without ear. While the treatment combination (60 x 25cm and 300 kg / ha) gave the yield of shelled weight per hectare Keywords: combination , corn P21, spacing, SP-36